The changing PM2.5 dynamics of global megacities based on long-term remotely sensed observations. (September 2020) - Zhang, Lili; Wilson, John P.; MacDonald, Beau; Zhang, Wenhao; Yu, Tao
Highlights: The 33 megacities contained 528 M people (15% of the global population) in 2018. Satellite data portray population and PM2.5 at fine spatiotemporal resolution. PM2.5 concentrations did not improve in these megacities from 1998 to 2018. 452 M residents face PM2.5 >10 μg/m 3 (WHO's upper limit for a healthy atmosphere). 163 M residents face PM2.5 >35 μg/m 3 (WHO's non-attainment air quality threshold). Abstract: Satellite observations show that the rapid urbanization and emergence of megacities with 10 million or more residents have raised PM2.5 concentrations across the globe during the past few decades. This study examines PM2.5 dynamics for the 33 cities included on the UN list of megacities published in 2018. These megacities were classified into densely (>1500 residents per km 2 ), moderately (300–1500 residents per km 2 ) and sparsely (<300 residents per km 2 ) populated areas to examine the effect of human population density on PM2.5 concentrations in these areas during the period 1998–2016. We found that: (1) the higher population density areas experienced higher PM2.5 concentrations; and (2) the megacities with high PM2.5 concentrations in these areas had higher concentrations than those in the moderately and sparsely populated areas of other megacities as well. The numbers of residents experiencing poor air quality is substantial: approximately 452 and 163 million experienced average annual PM2.5 levels exceeding 10 and 35 μg/m 3, respectively in 2016. We also examined PM2.5 trends during the past 18 years and predict that high PM2.5 levels will likely continue in many of these megacities in the future without substantial changes in their economies and/or pollution abatement practices. There will be more megacities in the highest PM2.5 pollution class and the number of megacities in the lowest PM2.5 pollution class will likely not change. Finally, we analyzed how the PM2.5 pollution burden varies geographically and ranked the 33 megacities in terms of PM2.5 pollution in 2016. The most polluted regions are China, India, and South Asia and the least polluted regions are Europe and Japan. None of the 33 megacities currently fall in the WHO's PM2.5 attainment class (<10 μg/m 3 ) while 9 megacities fall into the PM2.5 non-attainment class (>35 μg/m 3 ). In 2016, the least polluted megacity was New York and most polluted megacity was Delhi whose average annual PM2.5 concentration of 110 μg/m 3 is nearly three times the WHO's non-attainment threshold.